A Review on Ben Cao Gang Mu Ying Jiao Dui Zhao (《本草纲目影校对照》 A Contrast between the Photocopy and Collation of Compendium of Materia Medica) - Shunong Shen (Wolters Kluwer Health/LWW, 2019)
Ben Cao Gang Mu Ying Jiao Dui Zhao (《本草纲目影校对照》 A Contrast between the Photocopy and Collation of Compendium of Materia Medica), completed by Zhang Zhibin and Zheng Jinsheng, is the latest variorum on Ben Cao Gang Mu (《本草纲目》 Compendium of Materia Medica). Adopting five different Jinling editions as the master copy, the book carefully collates the complex contents on the original book by contrasting the photocopies with the supplement and correction, which makes it easy to use. What is more, full-form punctuation is used to mark the reference books and proper nouns, which is a big success feat in the research history of Ben Cao Gang Mu.